Health Belief Model Approach in Medication Adherence Compliance among Pulmonary Tuberculosis Patients - Hariyanto, Ari; Pamungkas, Rian Adi; Wahidi, Kemala Rita (International Journal of Nursing and Health Services (IJNHS), 2023)
Background: Medication adherence is one of the potential factors to increase the healing of TB patients and non-adherence. In addition, reducing the patient's recovery rate is also a threat to the occurrence of MDR TB. Objective: This study aims to analyze the influence of Perceived susceptibility, Perceived Benefits, Perceived Barriers, and Perceived Severity. on medication adherence of TB and MDR-TB patients at dr. Prawiranegara Drajat. Method: The method used in this research is quantitative with a cross-sectional approach. The sampling technique in this study was saturated sampling, where all members of the population were sampled, amounting to 125 TB and MDR-TB patients undergoing treatment at RSUD dr. Drajat Prawiranegara in 2021. Data analysis used multiple linear regression. Result: The results of this study obtained F-count value (5.210) > F-table (2.44) and sig 0.05 (0.002 0.05), then H0 is rejected, and H1 is accepted. This means that there is a significant effect between perceived susceptibility, perceived benefit, perceived barriers, and perceived severity on medication adherence in TB and MDR TB patients at the Regional General Hospital (RSUD) dr. Dradjat Prawiranegara Serang Regency. The findings in this study indicate that perceived susceptibility and perceived barriers are the lowest variables and have no effect on medication adherence in TB and MDR TB patients at the Regional General Hospital (RSUD) dr. Dradjat Prawiranegara Serang Regency. Recommendation: The clinical nurses need to consider the application of the health belief model to improve the medication adherence among pulmonary tuberculosis patients. Keywords: autogenic relaxation, head injury, pain